Sex-specific relationships among iron status biomarkers, athletic performance, maturity, and dietary intakes in pre-adolescent and adolescent athletes - Shoemaker, M. E.; Gillen, Z. M.; Mckay, B. D.; Bohannon, N. A.; Gibson, S. M.; Koehler, K.; Cramer, J. T. (Journal of the International Society of Sports Nutrition, 2019)
Background: The purpose of this study was to examine relationships among biomarkers of iron status, athletic performance, growth and development, and dietary intakes in pre-adolescent and adolescent male and female athletes. Methods: Two-hundred and forty-nine male (n = 179) (mean ± standard deviation for age = 12.0 ± 2.1 years, height = 156.3 ± 13.9 cm, and weight = 49.1 ± 16.5 kg) and female (n = 70) (12.0 ± 2.2 years, 152.4 ± 12.3 cm, 45.3 ± 14.5 kg) athletes volunteered for capillary blood sample, anthropometric, athletic performance, and dietary intake assessments. Outcomes included maturity offset from peak height velocity, percent body fat, estimated muscle cross-sectional areas, vertical jump height (VJ), broad jump distance (BJ), pro-agility time (PA), L-cone time, 20-yard dash time (20YD), power push up (PPU) force, dietary intakes, and ferritin, soluble transferrin receptor (sTfR), and hemoglobin (Hb) concentrations. Results: Athletic performance was consistently correlated with Hb in males (r = .237-.375, p < 0.001-0.05) and with sTfR (r = .521-.649, p < 0.001-0.004) and iron intake (r = .397-.568, p = 0.001-0.027) in females. There were no relationships between dietary intakes and ferritin, sTfR, or Hb (p > 0.05). After partialing out age and height, VJ, PA, LC, and 20YD remained correlated with Hb in males (|rHb,y.Age| = .208-.322, p = 0.001-0.041; |rHb,y.Height| = .211-.321, p = 0.001-0.038). After partialing out iron intake, PA and LC remained correlated with sTfR in females (|rsTfR,y.ironintake| = .516-.569, p = 0.014-0.028). Conclusions: Iron status biomarkers demonstrated sex-specific relationships with anaerobic exercise performance in youth athletes, which may be more dependent on maturity status and dietary intake than age. Moderate relationships between sTfR and athletic performance in adolescent female athletes emphasizes the importance of iron intake in this demographic.